HFB202E - Western Philosophy And Modern Thought [Falsafah Barat Dan Pemikiran Moden] December 2018/January 2019 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (2019)
First Semester Examination Academic Session 2018/2019 December 2018/January 2019